JPEG with quadtree adaptive partitioning : Loss analysis - Russo, Claudia Cecilia (1999)
In this paper two images compression techniques with loss based on the method used by the compression Standard Joint Photographic Experts Groups (JPEG) and on the Quadtree adaptive partitioning method are presented and compared, and the loss produced studied. The ba seline JPEG algorithm will be ana lyzed, and op timizations emphasizing quantification and not modifying the standard restrictions will be proposed. The results obtained from the generalization in classes of images with very different characteristics will be analyzed; and blocks size effect in conflicting areas such as the borders will be considered.